The controversial role of linoleic acid in cardiometabolic health: from molecular pathways to human studies - Berkowitz, Loni; Araneda, Paloma; Cofré, Glenda; Sara, Daniela; Olsen, Mariano; Urzúa, Isadora; Pérez, Druso; Rigotti, Attilio (Frontiers in Nutrition, 2026)
Unhealthy diets are major contributors to the global burden of non-communicable diseases, particularly cardiovascular disease and metabolic syndrome, where dietary fat quality plays a critical role. Among dietary fats, linoleic acid (LA)—the predominant omega-6 polyunsaturated fatty acid—has been at the center of a long-standing and evolving controversy. Initially promoted for its cholesterol-lowering properties, LA later became the focus of debate due to hypotheses suggesting pro-inflammatory and oxidative effects, which led to conflicting interpretations of its metabolic impact and inconsistent dietary guidelines over time. This review traces the origins and progression of this controversy, examining how shifts in biochemical understanding, experimental design, and population dietary patterns have shaped current perspectives on LA and cardiometabolic health. By integrating evidence from biochemical, preclinical, and human studies, we clarify the mechanistic and clinical bases underlying LA’s actions and re-evaluate its role in lipid metabolism, inflammation, and glucose regulation. Overall, most human evidence supports beneficial associations between LA exposure and cardiometabolic outcomes, though heterogeneity across studies underscores the relevance of dietary context, genetic background, and metabolic status. Understanding how the controversy emerged and evolved is essential to refine current recommendations for dietary fat and disease prevention.